Quantitative analysis of irregular channel shape effects on charge-trapping efficiency using massive 3D NAND data. (April 2023) - Park, Chanyang; Yoon, Jun-Sik; Nam, Kihoon; Jang, Hyundong; Park, Min Sang; Baek, Rock-Hyun
Abstract: The randomly fluctuating trap efficiency of taper-etched nanowire thin-film transistors was investigated by measuring a very large statistical ensemble of three-dimensional NAND flash memory cells. We made trapping in n-bit multi-level cells using incremental step pulse programming and observed the widening of the threshold voltage distribution caused by abnormal program cells. Further, we classified the components that broaden the threshold voltage distribution in both chip- and wafer-level measurements to analyze behaviors of the randomly fluctuating abnormal program cell. The variations in reading and programming operations are difficult to separate because they act simultaneously in the data reading and writing operations. For each pulse of the programming, the variations occur in reading for verification, in programming itself, and in reading after program completion. To analyze the inseparable variation, we used a method to extract only the intrinsic over-programming by removing variations in the read operation from the entire abnormal program cell. Using this extraction method, we could distinguish between the simultaneous read variation and over-programming. In particular, the unpredictable effect of the three-dimensional structure, such as the irregular shape and different radius due to the tapered channel hole profile from the nonideal etching process, was calculated and verified using experimental data. We quantitatively analyzed the experimental data one by one for each cell within the entire distribution, and each pulse of dozens in the programming scheme. This analysis provides quantitative information on the variations in charge-trapping efficiency and the threshold voltage distribution width by irregular-shaped tunneling layers.